An Online Neonatal Intensive-Care Unit Monitoring System for Hospitals in Nigeria - IDOWU, PETER ADEBAYO; ASAHIAH, FRANKLIN OLADIPO; BALOGUN, JEREMIAH ADEMOLA (IGI ﻿Global, 2020)
International Journal of Biomedical and Clinical Engineering, Volume 6 • Issue 1